2019
DOI: 10.1007/s12325-019-00900-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient Needs, Perceptions, and Attitudinal Drivers Associated with Obesity: A Qualitative Online Bulletin Board Study

Abstract: Introduction:To gain insights into the needs, attitudes, perceptions, and preferences of people living with obesity using an online bulletin board (OBB) study. Methods: The OBB is a moderated asynchronous online qualitative market research method that allows interactive discussion among participants. Participants were recruited via physician referral followed by screening questions to ensure eligibility and willingness to participate. The discussions in the OBB were moderated and allowed anonymized open answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…OBB online bulletin board, SML social media listening the study [12,19]. When the participating patients were contacted for debriefing at the end of the OBB session, the patients expressed agreement with the conclusions derived from the discussions and also expressed that they were very engaged throughout their participation in the study.…”
Section: Obbmentioning
confidence: 92%
“…OBB online bulletin board, SML social media listening the study [12,19]. When the participating patients were contacted for debriefing at the end of the OBB session, the patients expressed agreement with the conclusions derived from the discussions and also expressed that they were very engaged throughout their participation in the study.…”
Section: Obbmentioning
confidence: 92%
“…Qualitative research methods have often been considered complementary to quantitative methods and prudent use of such approaches may help develop a broader understanding of clinical realities [45]. We demonstrated that the OBB, being an asynchronous, moderated, closed online community platform, offers an optimal means to uncover patient insights for qualitative patient research, with both more common and rare disease patient populations [27][28][29]46].…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we used a qualitative OBB methodology to generate patient insights into disease perception, management and unmet needs associated with PVNS [27][28][29]. In our study, all the participants unanimously expressed that pain was a significant factor for emotional and psychological burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the interest and needs of patients vary with different types of chronic diseases, the topics involved in these discussion forums should also be based on the interests of the population group being targeted. For instance, Lanoye et al [ 59 ] found the importance of discussing the stigma and peer pressure related to obesity within a young adult population, whereas Cook et al [ 60 ] found that emotional support and use of medication are priorities in an older population with obesity. Therefore, the demographic background [ 11 , 61 , 62 ] and type of chronic diseases [ 7 ] are all factors potentially influencing the acceptability of a feature and should be considered when designing and evaluating web-based interventions.…”
Section: Discussionmentioning
confidence: 99%